2004
DOI: 10.1093/carcin/bgh228
|View full text |Cite
|
Sign up to set email alerts
|

BC200 RNA in invasive and preinvasive breast cancer

Abstract: BC200 RNA, a small functional RNA that operates as a translational modulator, has been implicated in the regulation of local synaptodendritic protein synthesis in neurons. Cell type-specific expression of BC200 RNA is tightly controlled such that the RNA is not normally detected in somatic cells other than neurons. However, the neuron-specific control of BC200 expression is deregulated in a number of tumors. We here report that BC200 RNA is expressed at high levels in invasive carcinomas of the breast. In norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 21 publications
1
110
2
2
Order By: Relevance
“…BC200 was previously speculated to be associated with invasion and migration in breast cancer. It was reported that BC200 was expressed at high levels in invasive carcinomas of the breast, and may potentially serve as a molecular tool in the diagnosis and/or prognosis of breast cancer (31). However, the results of the present study demonstrated that BC200 has no effect on the migration and invasion ability of ovarian cancer cells.…”
contrasting
confidence: 83%
“…BC200 was previously speculated to be associated with invasion and migration in breast cancer. It was reported that BC200 was expressed at high levels in invasive carcinomas of the breast, and may potentially serve as a molecular tool in the diagnosis and/or prognosis of breast cancer (31). However, the results of the present study demonstrated that BC200 has no effect on the migration and invasion ability of ovarian cancer cells.…”
contrasting
confidence: 83%
“…Digital images of tissue sections were acquired using a Sony 3CCD DKC-5000 camera (Sony, New York, NY) or a CoolSnap HQ cooled CCD camera mounted on a Microphot-FXA microscope (Nikon, Melville, NY) as described previously (56). …”
Section: Methodsmentioning
confidence: 99%
“…10,11 In breast cancer, invasive carcinoma reportedly expresses BC200 RNA at higher levels than normal tissues or benign tumors. 12 Moreover, overexpression of BC200 RNA in non-small-cell lung and colorectal cancers was recently reported to promote metastasis. 13,14 However, it is still unclear how deregulated BC200 RNA expression influences the metabolism of such cells, and how such changes influence disease.…”
Section: Introductionmentioning
confidence: 99%